Identifikasi Kualitas Air dan Pelatihan Teknik Penjernihan Air Sederhana di Desa Tanjung Menang, Kabupaten Ogan Komering Ilir - Wicaksono Anggun; Noviyanto Noviyanto; Alfia Rahma Kurnia; Kurratul Aini; Yustina Hapida; Rian Oktiansyah; Amin Nurokhman; Ummi Hiras Habisukan (Institut Pertanian Bogor, 2023)
Clean water is a basic need for society. However, the problem of clean water sources still occurs in the Ogan Komering Ilir (OKI) area of South Sumatra Province. The condition of the water being brownish and oily is an unresolved problem. One source that has the potential to disrupt water quality is the presence of factories around rivers. This community service activity aims to identify water quality and provide training to the community regarding river water management strategies and drilled wells as the primary water source for obtaining clean water, as well as increasing understanding and knowledge about clean water management with the Gravity-fed Filter Technique. The method of activities related to clean water quality is carried out in four stages, namely: 1) Location survey (cross-sectional), 2) Water sampling and laboratory analysis, 3) Education on water quality standards, and 4) Training on Gravity-fed Filter Techniques. The laboratory analysis showed that the water samples smelled fishy and were brownish and oily. In addition, the results of microbiological tests on water samples contained Coliform bacteria (sanitation indicator bacteria), which were outside the provisions of Minister of Health Decree No. 907/MENKES/SK/VII/2002 concerning clean water quality requirements. Through training activities using the Gravity-fed Filter technique, the pH and bacteria contained in the water can be reduced. Clean water management strategies using the Gravity-fed Filter technique can be used as a solution to improve clean water quality. Every society can apply the Gravity-fed Filter technique. Through this activity, society has managed water sources into clean water for daily needs.